Acute pancreatitis as an initial presentation of SLE: a case report - Benjamin Sachdev Manjit Singh, Sachdev; Teh Cheng Lay, Teh; Chuah Seow Lin, Chuah; Cheong Yaw Kiet, Cheong; Sharifah Aishah, Wan; Ahmad Tirmizi, Jobli (John Wiley & Sons, 2021)
Background: SLE is a complex multi- systemic autoimmune disease capable of affecting any organ system with varying presentations. Abdominal pain is a common manifestation of SLE and is reported to occur in about 8% to 40% of patients with SLE. The causes of abdominal pain are varied and require accurate assessment. Acute Pancreatitis is a cause of abdominal pain and is a rare initial SLE presentation. It is characterized by abdominal pain and raised serum amylase levels. We would like to report a patient diagnosed with SLE following an initial presentation of Acute Pancreatitis, which was complicated with a pancreatic pseudocyst. Case Report: The patient is an 18- year- old lady with no previous known medical illness who presented with a one day history of acute central abdominal pain radiating to the back. This was preceded by a two week history of fever and non- productive cough. Further history revealed that she had alopecia, malar rash and painless oral ulcers one year before this presentation but did not seek medical attention. Physical examination revealed a tender and distended abdomen. Blood investigations showed leukopenia, elevated amylase with a positive Anti- nuclear antibody, and coombs test. She was admitted to the ICU and treated with intravenous cyclophosphamide, methylprednisolone, immunoglobulin, and antibiotics. During her follow- up a month after discharge, she was found to have recurrent abdominal pain and distension. A repeated CT Abdomen showed a pancreatic pseudocyst, and she underwent an endoscopic cystogastrostomy. Currently, she is on regular follow- up and is currently maintained on Hydroxychloroquine, Azathioprine, and Prednisolone. Conclusion: In summary, Acute Pancreatitis is a relatively rare initial manifestation of SLE. The causes of Acute Pancreatitis are varied, and it is essential to recognize and differentiate Acute Pancreatitis due to active SLE from other causes as it may affect treatment decisions and subsequent mortality outcomes.